Counseling on Oil Bodies Utilization and Mangrove Seed Conservation in Pramuka Island, North Thousand Islands District, Thousand Islands Regency - Buntora Pasaribu; Kalysta Fellatami; Lantun P. Dewanti; Ibnu Faizal (Farmers: Journal of Community Services, 2023)
Oil bodies play an important role in storing energy in plants and animals. The structure of oil bodies consists of triacylglycerol surrounded by a layer of phospholipids and bound by unique proteins. Oil bodies are widely found in various organisms such as algae, soil plant,  water seeds plants, flowers, pollen, and animals. Mangrove seeds, also known as "bakau" plants, are a unique aquatic plant that can grow in water bodies throughout the world, including Indonesia, which has a high oil content of 40-70%. Mangrove seeds are a potential alternative biomass that can be used for biodiesel material. Therefore, the aim of this community service is to provide education on the oil bodies found in mangroves and the conservation of mangrove seeds, in the form of mangrove mitigation on Pramuka Island. This outreach program can provide knowledge to the community, particularly mangrove farmers on Pramuka Island, on how to utilize mangrove seeds as alternative food and biofuel sources to improve their future economic income. This outreach program also educates the local community to preserve the mangrove seeds for their sustainability in the future.